Integer Linear Programming Models for the Containership Stowage Problem. (14th October 2020) - Zhu, Huiling; Ji, Mingjun; Guo, Wenwen
Abstract : This study deals with the containership stowage problem, determining how to stow containers to the containership slots. To improve the containership operational efficiency and meet the containership seaworthy requirements, a basic model is proposed for the simplified containership stowage problem. And then, it is extended by incorporating more practical considerations, which are progressively embedded in extensive models for different scenarios. These integer linear programming models aim to minimize the number of overstows under the restriction of the mechanical factors, the physical structure, and the stowing rules. The experimental results show that the models have strong scalability for various scenarios.